Povezanost strukture diplomantov terciarnega izobraževanja z gospodarsko razvitostjo - analiza evropskih držav - Hojs Potočnik, Jarmila (Naše gospodarstvo, 2013)
In this paper the correlation between the structure of graduates by study fields (using ISCED 1997 classification) and real GDP per capita is analyzed for the 25 countries of the European Union, Iceland, Norway, and Switzerland. Although the relationship between education and economic development has been the topic of numerous studies, results are often contradictory, and only a few studies have analyzed the structure of graduates by study fields of education. Our research results suggest that the structure of graduates by study fields correlates with the GDP per capita, where some negative and some positive correlations are identified.
Keywords: education; izobraževanje; visoko šolstvo; diplomanti; economy; gospodarstvo; ekonomski razvoj; Europe; Evropa